Solution
Gievn the equation below
![4y-9=x^2-6x](https://img.qammunity.org/2023/formulas/mathematics/college/nu0irymsgm5kajiysmfrg8l0v788rreci9.png)
To find the vertex and focus of the given equation, we apply the parabola standard equation which is
![4p(y-k)=(x-h)^2](https://img.qammunity.org/2023/formulas/mathematics/college/n4m440verw47cc0s0yjkarjn6ecqlbm1mf.png)
Where p is the focal length and the vertex is (h,k)
Rewriting the equation in standard form gives
![\begin{gathered} 4y-9=x^2-6x \\ 4y=x^2-6x+9 \\ 4y=x^2-3x-3x+9 \\ 4y=x(x-3)-3(x-3) \\ 4y=(x-3)^2 \\ 4(1)(y-0)=(x-3)^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kc46a9cf76s0wucb8v5ezt0a8yd5sjk55c.png)
Relating the parabola standard equation with the given equation, the vertex of the parabola is
![\begin{gathered} x-3=0 \\ x=3 \\ y-0=0 \\ y=0 \\ (h,k)\Rightarrow(3,0) \\ p=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wdqx5g9ji5w5pvvepjc2t0duc6jpbnyg4l.png)
Hence, the vertex is (3,0)
The focus of the parabola formula is
![(h,k+p)](https://img.qammunity.org/2023/formulas/mathematics/college/pgc8wpzlnt2md4552fmrs5c4cjcpu449eg.png)
Where
![\begin{gathered} h=3 \\ k=0 \\ p=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/izzi79bqo0gpmb6br92tu460cu3uhochwv.png)
Substitute the values of h, k and p into the focus formula
![(h,k+p)\Rightarrow(3,0+1)\Rightarrow(3,1)](https://img.qammunity.org/2023/formulas/mathematics/college/emi6y5asl0ia716yxltsnnb1nmqgg3hu0d.png)
Hence, the focus is (3, 1)